Criminal Implementation Against Cyber Actors Crime Phising - Vicha Kartika; Budi Sastra Panjaitan (Universitas Islam Malang, 2023)
Indonesia is getting more and more advanced day by day, including in the field of electronics. One of the electronic devices is a computer. Many people use computers in their daily activities, which are growing rapidly. Apart from these activities, there are various cases of internet abuse that have become very widespread, ranging from fraudulent fraud, online fraud, defamation, etc. With the ratification of Law no. 11 of 2008 concerning information and electronic transactions jo. Article 27 paragraph (3) Law no. 11 of 2008, so the regulation on the use of information and electronic transactions has received legal action. With this law, crimes in the form of cyberspace (cyber crime) become easier to be legally processed, in cases of cyber crimes it becomes easier, especially in the form of phishing. Keywords: Indonesia, Internet, Electronics